Immigrant Game Birds from Rajasthan - Sankhala, K. S. (Indian Forester, 1963)
Grey partridge and common Indian sand grouse are the indigenous game birds, very commonly found in the North-western desert parts of Rajasthan. The paper describes the introduction of these birds in the hot arid lands of Nevada in U.S.A.